Reconstructing the Concept of Ahliyyah (Legal Capacity) for Autonomous AI Entities in Islamic Jurisprudence: A Critical Analysis of Digital Contracts and Muamalah Principles - Nasiri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
The rapid advancement of Autonomous Artificial Intelligence (AI) has challenged the traditional human-centric framework of Ahliyyah (legal capacity) in Islamic jurisprudence. This study aims to investigate the legal status of AI entities in executing digital contracts and to propose a reconstruction of Ahliyyah that accommodates non-human autonomous agents. Using a qualitative-normative legal research method with a Maqashid al-Shari’ah approach, this study analyzes classical Fiqh texts alongside modern technological realities. The findings reveal that while AI lacks metaphysical consciousness (Ruh), it possesses "Functional Discernment" (Tamyiz al-Waza’ifi) capable of fulfilling the technical requirements of Ijab (offer) and Qabul (acceptance). The research proposes the recognition of "Digital Personality" (Syakhshiyah Raqmiyah) as a new legal category, shifting the locus of legal capacity from biological existence to functional autonomy. This reconstruction ensures that AI-driven transactions remain valid under Sharia while providing a clear framework for Dhaman (liability) and accountability. This study contributes to the development of a "Digital Fiqh" that harmonizes Islamic law with the global digital economy.